The TTP, the inclusion of new members and the future of APEC - Aquino Rodríguez, Carlos Alberto (2014)
TPP negotiations are expected to finish this year but this seems to be difficult now. It would be one of the most ambitious liberalizations agreements as it wouldn’t leave any sector of the economy out of this process. Furthermore, it is considered that TPP would be a step to complete the process of liberalization between the 21 APEC economies.In this article the process of liberalization of the TPP is analyzed, starting first with a description of what TPP is; second we will see the points that are in negotiations in the TPP, especially the most contentious ones; third it is seen what Peru can gain from this process; in fourth term it is seen about the possible inclusion of new members, analyzing the specific case of Taiwan and China; fifth what about the TPP and the future of APEC and finally some conclusions are given.